2005
DOI: 10.1177/0018726705052182
|View full text |Cite
|
Sign up to set email alerts
|

Rational or demoralized responses to work restructuring in Hong Kong?

Abstract: A B S T R AC TOwing to the paucity of data demonstrating workers' reactions to work restructuring, the study examines possible reactions in terms of job performance, attendance at training, and voicing of discontent. It predicts the effects of work restructuring and background characteristics with reference to the exit-voice-loyalty model and demoralization theory. A telephone survey of a random sample of households collected data from 1176 workers in Hong Kong. Supportive of the demoralization theory, work re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 87 publications
2
9
0
Order By: Relevance
“…This finding is contrary to the expectation of strain theory. The negative effect of strain tends to reflect the demoralizing effect of strain, which is consistent with previous research (Cheung, 2005;Ngai and Cheung, 2005). Accordingly, strain generally discourages the person from engaging in activities, including delinquency and substance use.…”
Section: Discussionsupporting
confidence: 92%
“…This finding is contrary to the expectation of strain theory. The negative effect of strain tends to reflect the demoralizing effect of strain, which is consistent with previous research (Cheung, 2005;Ngai and Cheung, 2005). Accordingly, strain generally discourages the person from engaging in activities, including delinquency and substance use.…”
Section: Discussionsupporting
confidence: 92%
“…According to structural fit theory, these resources may not fit the Hong Kong way of life. For instance, work experience before migration may not be relevant to work in Hong Kong, probably because of discrepancies in the work system between Hong Kong and the mainland, such as the levels of post‐industrialisation, job security, and the requirements for worker competitiveness and quality performance (Cheung, ; Chiu and Lui, ). Accordingly, work on the mainland is less competitive and less skilled, while workers receive more benefits and protection from their work organisations (Lin and Lai, ; Xiang and Li, ).…”
Section: Discussionmentioning
confidence: 99%
“…More specifically, the concept of job alienation is a psychological change that results in an imbalance between the effort made and the results achieved. Innovative changes in the tourism distribution system have led to changes in the development of the operator, new skills and changes inherent in the nature of the business and put more pressure on the employees (Di Pietro and Pizam, 2008), and in addition, they reveal the feeling of alienation (Cheung, 2005). In the work of Sharma and Gassenheimer (2009) and in other studies, it has been found that cannibalization expected by the sales representatives of the presence of the internet option increases the uncertainty in the workplace (Berger, 1979(Berger, , 1986Planalp and Honeycutt, 1985;Shannon and Weaver, 1949).…”
Section: Service Cannibalization Perception Of Sales Representatives mentioning
confidence: 99%